(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This thesis investigates Frank Herbert’s unique contribution to the growth of science fiction. By broadening the thematic variation beyond technological speculation to include ecological, political, psychological, and religious aspects, particularly human-environment interactions and power structures with resource-based economies, Herbert basically transformed the genre. Also, author raised science fiction to a tool for systematic thinking and philosophical reflection by incorporating aspects of Jungian psychology, Eastern philosophy, and linguistic invention. This thesis claims that Herbert’s methods represent a turning point in the development of science fiction, transforming it into a mature and intellectually rich literary form.